Association between self-reported vision and mental well-being: a cross-sectional secondary analysis of Health Survey for England data - Marc S Tibber; Michael D Crossland; Tessa M Dekker (BMJ Open)
Objectives Eye disease and vision impairment are known to be associated with reduced mental well-being, but less is known about the well-being of people with near-normal levels of vision. Here, we examined the association between self-reported eyesight and mental well-being, controlling for eye disease, mental ill-health and demographic factors, for adults with a wide range of age and vision.Design Population-based cross-sectional study.Participants 7705 adults (56% women; median age 49 years, range 16–104 years) who participated in the Health Survey for England 2013, self-reported their eyesight status and completed the Warwick-Edinburgh Mental Well-Being Scale.Primary outcome measure Mental well-being, controlling for self-reported mental ill health, self-reported eye disease, age, sex, socioeconomic group and ethnic origin.Results Poorer self-reported eyesight was strongly associated with lower mental well-being (univariate linear model, F(4,7700)=94.7, p<0.001) and explained 5% of the variance in the outcome variable (R2=0.047). Relative to reporting ‘poor’ vision, each subsequent level of vision predicted better well-being, with the exception of ‘fair’ vision, which was not significantly different from ‘poor’ reported vision. This association remained significant after controlling for self-reported mental ill health, self-reported eye disease, age, sex, socioeconomic group and ethnic origin.Conclusions Self-reported eyesight is strongly associated with mental well-being, irrespective of whether people have vision impairment or a diagnosed eye disease. This relationship exists in people with and without mental ill-health. Mental well-being should be considered in people with reduced eyesight, regardless of whether they have a diagnosed eye disease or mental ill-health. Interventions which improve vision may have a positive impact on mental well-being.